P097 Are patients in rural communities interested in online sexual health services?. (30th June 2016) - Pearce, Amy; Penrose, Rachael; Palmer, Joanne; Perrin, Thomas; Keane, Frances
Abstract : Background/introduction: People do not attend Genitourinary Medicine (GUM) services for reasons including cultural beliefs and stigma. In Cornwall geographical isolation, poor transport and local Council budgetary cuts to peripheral clinics also limit access. Aim(s)/objectives: To ascertain whether patients would use online services to book appointments and/or order home testing kits. Methods: An anonymised questionnaire survey of GUM patients. Data was recorded into an Excel spreadsheet and analysed using SPSS. Results: 248 questionnaires were returned from women(59.7%) and men(40.3%) aged 13–72 years. 154 (62.3%) were previous attendees and 234 (94.7%) had internet access. Confidentiality was more important than face-to-face consultations or 24hr access to testing (p = 0.036 ). Previous GUM attendees were more likely to book appointments compared to new users who would attend a drop-in clinic (p = 0.011 ). Discussion/conclusion: Patients would be willing to consider online services. Home testing could reach those who struggle to access clinics through lack of transport and appealed most to patients >18years, a group that should be targeted.